Evaluation of Ir-based modifiers in the simultaneous determination of As, Bi, Pb, Sb, and Se in milk by graphite furnace atomic absorption spectrometry - Freschi, Gian P. G. [UNESP]; Freschi, Carolina D. [UNESP]; Oliveira, Silvana R. [UNESP]; Gomes Neto, José A. [UNESP] (My University, 2006)
Different modifiers (IrCl3, W+IrCl3, Zr+IrCl 3) and coatings (Ir, W-Ir, Zr-Ir) were evaluated for the simultaneous determination of arsenic, bismuth, lead, antimony, and selenium in milk by graphite furnace atomic absorption spectrometry using the 'end-capped' transversely heated graphite atomizer (THGA). Integrated platform, pretreated with Zr-Ir as permanent modifier, was elected as the optimum surface modification resulting in up to 250 firings. Two additional recoatings were possible without significant changes in the analytical performance (750 firings). For 20 μL of matrix-matched standard solutions using diluted (1:10) milk samples, typical correlation coefficients between integrated absorbance and analyte concentration (5.00-20.0 μg/L) was always better than 0.999. The levels of the analytes found in commercial milk samples were lower than the limit of detection: 2.9 μg/L As, 2.9 μg/L Bi, 1.8 μg/L Pb, 1.9 μg/L Sb, and 2.5 μg/L Se. Recoveries were found within the following intervals: 88-114% for As, 89-118% for Bi, 89-113% for Pb, 91-115% for Sb, and 92-115% for Se. The relative standard deviations (n = 12) were ≤2% (As), ≤ 5% (Bi), ≤ 1.4% (Pb), ≤ 3% (Sb), and 5% (Se), and the respective calculated characteristic masses were 54 pg As, 55 pg Bi, 40 pg Pb, 56 pg Sb, and 51 pg Se.